Reassessing critical maternal antibody threshold in RhD alloimmunization: a 16‐year retrospective cohort study. (6th November 2014) - Walsh, C. A.; Doyle, B.; Quigley, J.; McAuliffe, F. M.; Fitzgerald, J.; Mahony, R.; Higgins, S.; Carroll, S.; McParland, P.
<x xml:space="preserve">Abstract</x> This article has been selected for Journal Club. Click here to view slides and discussion points.